2009
DOI: 10.1080/01902140902759290
|View full text |Cite
|
Sign up to set email alerts
|

Signal Transduction Pathways Linking the Activation of Alveolar Macrophages With the Recruitment of Neutrophils to Lungs in Chronic Obstructive Pulmonary Disease

Abstract: Chronic obstructive pulmonary disease (COPD) is a major and increasing global health problem. It is predicted by the World Health Organization to become the third most common cause of death and the fifth most common cause of disability in the world by 2020. COPD is a complex inflammatory disease involving several types of inflammatory cells and multiple inflammatory mediators. Although abnormal numbers of inflammatory cells such as macrophages, dendritic cells, neutrophils, and T lymphocytes have been document… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 169 publications
0
50
0
1
Order By: Relevance
“…Since the promoter region in the IL-1β gene contains binding motifs for AP-1 [35,36] inhibition of its activation will result in reduced IL-1β production. Having in mind that several studies have identified IL-1β as one of the major cytokines driving neutrophil accumulation in lung tissue [26][27][28][29]39,40], inhibition of AP-1 activation and consequent IL-1β production by alveolar macrophages seems to be a sufficient and likely mechanism by which azithromycin reduced neutrophil accumulation in the lungs following LPS challenge (concept summarized in Fig. 9).…”
Section: Discussionmentioning
confidence: 98%
“…Since the promoter region in the IL-1β gene contains binding motifs for AP-1 [35,36] inhibition of its activation will result in reduced IL-1β production. Having in mind that several studies have identified IL-1β as one of the major cytokines driving neutrophil accumulation in lung tissue [26][27][28][29]39,40], inhibition of AP-1 activation and consequent IL-1β production by alveolar macrophages seems to be a sufficient and likely mechanism by which azithromycin reduced neutrophil accumulation in the lungs following LPS challenge (concept summarized in Fig. 9).…”
Section: Discussionmentioning
confidence: 98%
“…Generally, bacteria and viruses that survive host defense mechanisms and proliferate within the animal body are the main triggering factors of inflammation and PMNs are directly and indirectly responsible for most of the observed pathological changes and lesions [36,37]. Mobilization of PMNs in the inflamed tissue is modulated by interactions among leucocytes and cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Mobilization of PMNs in the inflamed tissue is modulated by interactions among leucocytes and cytokines. During the acute-phase response of the inflammatory process caused by infectious agents in ruminants and humans, inflammatory cytokines such as interleukin (IL)-1b, TNF-a, and IL-8, secreted by a variety of immune and nonimmune cell types, induce intense PMN mobilization and an increased inflammatory response [36,37]. PMN mobilization does not always effectively combat the infection and may also contribute to the development of lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Initially recruited neutrophils undergo apoptosis and alveolar macrophages engulf these cells, a process that results in the production of active TGFb (Fadok et al, 1998). A number of key molecules have been identified in the process of inflammatory cell recruitment and include selectins, integrins, cytokines, and growth factors, the innate immune system including TLRs, surfactant protein A (SPA) and SPD, as well as components of the extracellular matrix (Reidy and Wright, 2003;Reutershan and Ley, 2004;Craig et al, 2009;Murugan and Peck, 2009).…”
Section: Leukocyte Recruitmentmentioning
confidence: 98%